Opciones terapéuticas actuales en el manejo de la coledocolitiasis asociada a colecistolitiasis - Lembach J., Hanns; Cuneo B., Nicole; Montenegro U., Cristián; Muñoz D., Pablo; Valladares H., Hector; Berger F., Zoltan; Sauré M., Alexandre; Castillo K., Jaime; Díaz J., Juan Carlos (Revista Hospital Clínico Universidad de Chile, 2017)
The term Choledocholithiasis refers to the presence of biliary stones in the extrahepatic bile ducts, which are found in 5 to 10% of patients undergoing cholecystectomy for gallstones. Nowadays, with the adoption of the laparoscopic cholecystectomy(LC) as a standard, multiple minimally invasive treatment options for bile duct stones are feasible, with no consensus to date on the procedure of choice. The two stage endoscopic techniques involve the use of Endoscopic Retrograde Cholangiopancreatography(ERCP) before or after performing a LC, which has the main advantage of separating the bile duct procedure from the LC. However, the need for two separate anesthesia times, the possibility of blank or failed ERCP, and the chance for calculi migration between procedures increase the length of hospital stay and associated costs. The single stage procedures include the Laparoscopic Bile Duct Exploration (LBDE), and more recently, the performance of a laparoscopy guided intraoperative ERCP(Rendez Vous). The LBDE, when performed by an experienced surgical team, is an effective and safe technique. Nonetheless, it is considered a technically demanding procedure, whose results cannot be extrapolated to the general surgical community. Recently, the Rendez Vous has become a treatment alternative that simplifies both the surgical and the endoscopic procedures, decreases morbidity, and requires a single anesthesia time. On the downside, Rendez Vous technique involves complex operating room (OR) logistics, requiring both a trained surgical and endoscopic team at the same time.